2014
DOI: 10.5367/ihe.2014.0233
|View full text |Cite
|
Sign up to set email alerts
|

Refocusing — Building a Future for Entrepreneurial Education and Learning

Abstract: The field of entrepreneurship has struggled with fundamental questions concerning the subject's nature and purpose. To whom and to what means are educational and training agendas ultimately directed? Such questions have become of central importance to policy makers, practitioners and academics alike. There are suggestions that university business schools should engage more critically with the lived experiences of practising entrepreneurs through alternative pedagogical approaches and methods, seeking … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(17 citation statements)
references
References 72 publications
0
16
0
1
Order By: Relevance
“…This reflection, similar to that concluded by Cope (2005) demonstrates the ongoing existence of 'reflective practitioners', (pp. 380;Higgins and Galloway, 2014). Three of the four Principals, for example, were very clearly highly qualified and experienced in their respective technologies, what we might classify as 'known-knowns'.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This reflection, similar to that concluded by Cope (2005) demonstrates the ongoing existence of 'reflective practitioners', (pp. 380;Higgins and Galloway, 2014). Three of the four Principals, for example, were very clearly highly qualified and experienced in their respective technologies, what we might classify as 'known-knowns'.…”
Section: Discussionmentioning
confidence: 99%
“…It is through reflection he argues that experience is turned into learning. Higgins & Galloway (2014) add weight to the importance of reflection in practitioner learning, stating 'the use of reflexivity to critique practice invites entrepreneurs to question claims of existing knowledge and the process of knowledge creation. ', (p453).…”
Section: Introductionmentioning
confidence: 99%
“…Other studies have suggested entrepreneurial teachers demonstrate entrepreneurial behaviour in their actions (Gibb, 2011;Higgins et al, 2014). Innovativeness in teaching has been related to creative classroom behaviours and a constructivist teaching approach (Ucus and Acar, 2018).…”
Section: Entrepreneurial Teaching Methodsmentioning
confidence: 99%
“…These challenges are long-standing (Gibb, 2002(Gibb, , 2005Higgins and Galloway, 2014), with Kirby (2004) calling for a paradigm change that better considers competency and mindset development, and Pittaway and Edwards (2012) for assessment that is more innovative, reflective and inclusive of stakeholders: 'There is a need for further research that explores assessment practice in entrepreneurship education in disciplines outside of business schools' (Pittaway and Edwards, 2012: 794). Krueger and Welpe (2014) engaged with an evolving series of neuroscience discussions, concluding that, while research into the learning brain was hard to follow, it could offer valuable insights related to entrepreneurial competency development.…”
mentioning
confidence: 99%